The effect of increased levels of lead in serum on several antioxidants parameters assed among workers from a large private electrical generator company - Mehdi, Wesen Adel; Mehde, Atheer Awad (European Journal of Chemistry, 2014)
Lead poisoning occurs when lead builds up in the body, regularly over a period of months or years. Insignificant amounts of lead can cause serious health complications. The main objective of this study is to determine the effect of gases rising from electric generators and the lead-induced oxidative stress and adversarial health properties by biochemical markers in Iraqi workers employed on the operation of diesel generators mainly increased lead poisoning symptoms. Serum lead, advanced oxidation protein products (AOPP), total antioxidant activity (TAA), malondialdehyde (MDA), and other biochemical parameters were analysed in fifty workers in a large private electrical generator. The results of the study showed a significant elevation in lead, AOPP and MDA activities in Iraqi workers employed on the operation of diesel generators in association to healthy control samples. The results showed that elevated serum lead has a significant correlation with oxidative stress, and biochemical markers that may be help to detect impairment in the body function in lead exposed workers.